2018
DOI: 10.1097/qai.0000000000001715
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Virological Suppression Among Young HIV-Positive Adults in Botswana

Abstract: Young adults in Botswana are significantly less likely to have undetectable HIV-1 RNA load compared with older adults. In the era of broad scale-up of ART, interventions able to diagnose young adults living with HIV and link them to effective therapy are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 22 publications
(18 reference statements)
0
11
0
Order By: Relevance
“…According to gender, females are more likely to experience virological success than men 80.9% vs 75.9% respectively, p = 0.013). Even though the recent CAMPHIA study reported a relatively higher VS in men than women (80.1% vs 79.2%) [9], data from many studies suggest that men are likely to experience virological failure than females [4, 15]. This can be justified by their high risk related behavioural patterns.…”
Section: Discussionmentioning
confidence: 99%
“…According to gender, females are more likely to experience virological success than men 80.9% vs 75.9% respectively, p = 0.013). Even though the recent CAMPHIA study reported a relatively higher VS in men than women (80.1% vs 79.2%) [9], data from many studies suggest that men are likely to experience virological failure than females [4, 15]. This can be justified by their high risk related behavioural patterns.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we estimated HIV incidence using a baseline cross-sectional sample from the Botswana Combination Prevention Project (BCPP; the Ya Tsie study) [ 2 , 38 , 39 ]. BCPP is an ongoing pair-matched, cluster-randomized clinical trial in 30 rural and peri-urban communities across Botswana.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the high prevalence of HIV/AIDS in Africa, the Highly Active Anti-retroviral Therapy (HAART) coverage is still low due to some reasons (2). In Africa, an estimated 66% of eligible people living with HIV were not receiving HAART in 2013 (3), only 45% of adults living with HIV were reported to know their HIV status, 86% of diagnosed persons were initiated on HAART, and an estimated 76% of persons on ART had achieved HIV viral load suppression in 2013 (4). The Uganda Population-based HIV Impact Assessment (UPHIA) results revealed that the country has made significant progress in reducing the HIV prevalence from 7.3% in 2011 to 6% in 2017.…”
Section: 0: Backgroundmentioning
confidence: 99%